Analysis of Improved Production Practices in Small holder Natural Rubber Plantation for Sustainable Natural Rubber Industry in Nigeria - Yuniyus Dengle, Giroh; Musa, Evelyn; Yustus, Sunday Francis (European Journal of Applied Sciences, 2020)
The decline in natural rubber production was a consequence of combined effects of the civil war and the oil boom era. Successive governments in the country responded through various policies and programme to address the poor performance of the natural rubber industry. The success of the industry will largely depend on small holder rubber farmers adopting the improved production practices. This study was therefore conducted to examine the Improved Production Practices in Small holder Natural Rubber Plantations for Sustainable Natural Rubber Industry in Nigeria. The specific objectives were to describe the socio- economic characteristics of respondents; identify improved production practices adopted for natural rubber production and examine factors influencing production . Data were collected on 296 small scale rubber farmers and analyzed using descriptive statistics and inferential statistics. Results revealed that respondents are relatively old with the mean age of 48 years with mean family size of 5 people and are smallholder farmers with mean farm size of 1.7 hectares and with mean experience of 16 years. Analysis on improved practices among respondents showed that 72.64% adopted tapping equipment maintenance, slashing of plantation (57.43%), fire traces (65.88%) while 37% of the respondents adopted alternate daily tapping. Furthermore, share arrangement was dominant mode of engagement for latex exploitation among respondents (57.09%). Exotic clones and NIG800/NIG900 series were used as the major planting materials while rubber +cassava, rubber +yam and rubber + plantain were the major rubber based cropping systems adopted by respondents. Cobb-Douglas production function analysis indicated that coefficient of multiple determination (R2) of 0.6303implied that 63.03% of the variations in output of the respondents were explained by the variables in the model. Farm size, improved planting materials, labour and supervision were factors influencing adoption of improved production among respondents